) Use the Laplace transform to solve the following initial value problem: y′′−6y′+9y=0y(0)=4,y′(0)=2 Using Y for the Laplace transform of y(t), i.e., Y=L{y(t)}, find the equation you get by taking the Laplace transform of the differential equation (s^2-6s+9)Y-4s+22 equation editorEquation Editor =0 Solve for Y(s)= (4s-22)/(s^2-6s+9) equation editorEquation Editor write the above answer in its partial fraction decomposition, Y(s)=As+a+B(s+a)2 Y(s)= equation editorEquation Editor + equation editorEquation Editor Now, by inverting the transform, find y(t)= equation editorEquation Editor .

Respuesta :

Answer:

[tex]y(t)=2e^{3t}(2-5t)[/tex]

Step-by-step explanation:

Let Y(s) be the Laplace transform Y=L{y(t)} of y(t)

Applying the Laplace transform to both sides of the differential equation and using the linearity of the transform, we get

L{y'' - 6y' + 9y} = L{0} = 0

(*) L{y''} - 6L{y'} + 9L{y} = 0 ; y(0)=4, y′(0)=2  

Using the theorem of the Laplace transform for derivatives, we know that:

[tex]\large\bf L\left\{y''\right\}=s^2Y(s)-sy(0)-y'(0)\\\\L\left\{y'\right\}=sY(s)-y(0)[/tex]

Replacing the initial values y(0)=4, y′(0)=2 we obtain

[tex]\large\bf L\left\{y''\right\}=s^2Y(s)-4s-2\\\\L\left\{y'\right\}=sY(s)-4[/tex]

and our differential equation (*) gets transformed in the algebraic equation

[tex]\large\bf s^2Y(s)-4s-2-6(sY(s)-4)+9Y(s)=0[/tex]

Solving for Y(s) we get

[tex]\large\bf s^2Y(s)-4s-2-6(sY(s)-4)+9Y(s)=0\Rightarrow (s^2-6s+9)Y(s)-4s+22=0\Rightarrow\\\\\Rightarrow Y(s)=\frac{4s-22}{s^2-6s+9}[/tex]

Now, we brake down the rational expression of Y(s) into partial fractions

[tex]\large\bf \frac{4s-22}{s^2-6s+9}=\frac{4s-22}{(s-3)^2}=\frac{A}{s-3}+\frac{B}{(s-3)^2}[/tex]

The numerator of the addition at the right must be equal to 4s-22, so

A(s - 3) + B = 4s - 22

As - 3A + B = 4s - 22

we deduct from here  

A = 4 and -3A + B = -22, so

A = 4 and B = -22 + 12 = -10

It means that

[tex]\large\bf \frac{4s-22}{s^2-6s+9}=\frac{4}{s-3}-\frac{10}{(s-3)^2}[/tex]

and

[tex]\large\bf Y(s)=\frac{4}{s-3}-\frac{10}{(s-3)^2}[/tex]

By taking the inverse Laplace transform on both sides and using the linearity of the inverse:

[tex]\large\bf y(t)=L^{-1}\left\{Y(s)\right\}=4L^{-1}\left\{\frac{1}{s-3}\right\}-10L^{-1}\left\{\frac{1}{(s-3)^2}\right\}[/tex]

we know that

[tex]\large\bf L^{-1}\left\{\frac{1}{s-3}\right\}=e^{3t}[/tex]

and for the first translation property of the inverse Laplace transform

[tex]\large\bf L^{-1}\left\{\frac{1}{(s-3)^2}\right\}=e^{3t}L^{-1}\left\{\frac{1}{s^2}\right\}=e^{3t}t=te^{3t}[/tex]

and the solution of our differential equation is

[tex]\large\bf y(t)=L^{-1}\left\{Y(s)\right\}=4L^{-1}\left\{\frac{1}{s-3}\right\}-10L^{-1}\left\{\frac{1}{(s-3)^2}\right\}=\\\\4e^{3t}-10te^{3t}=2e^{3t}(2-5t)\\\\\boxed{y(t)=2e^{3t}(2-5t)}[/tex]

ACCESS MORE